Penurunan Tingkat Insomnia Setelah diberikan Terapi Rendam Air Hangat pada Lansia - Rahma Aprilia; Ricky Riyanto Iksan; Sri Atun Wahyuningsih (MAHESA : Malahayati Health Student Journal, 2022)
ABSTRACT Insomnia in the elderly is a problem that is quite high with increasing age, including groups who experience insomnia problems due to physical changes and social environmental conditions that have an impact on health problems. The purpose of this study has been identified the application of warm water soak therapy on the feet to reduce insomnia levels in the elderly. This research method is a case study design research, which is a form of research (inquiry) or case studies and interventions about a problem that has a specificity (particularity). The results of the research conducted showed a decrease in the level of insomnia in the elderly with insomnia after being given warm water soak therapy on the feet from severe insomnia to mild-moderate insomnia, mild-moderate insomnia to no insomnia, and severe insomnia to no insomnia. Evidenced by the results of the first respondent experienced a decrease in insomnia from 18 to 15, the second respondent experienced a decrease in insomnia from 18 to 14, the third respondent experienced a decrease in insomnia from 18 to 11, and the fourth respondent experienced a decrease in insomnia from 15 to 11. Conclusions from the intervention study of warm water soak therapy on the feet in the elderly has shown a significant reduction in insomnia levels. Keywords: Elderly, Insomnia, Warm Water Soak ABSTRAK Insomnia pada lansia merupakan masalah yang cukup tinggi dengan bertambahnya usia lansia termasuk golongan yang mengalami masalah insomnia akibat perubahan fisik dan keadaan sosial lingkungan sehingga berdampak pada masalah kesehatan. Tujuan penelitian ini teridentifikasi penerapan terapi rendam air hangat pada kaki terhadap penurunan tingkat insomnia pada lansia. Metode penelitian ini adalah penelitian case study design yaitu suatu bentuk penelitian (inquiry) atau studi kasus dan intervensi tentang suatu masalah yang memiliki sifat kekhususan (particularity). Hasil penelitian yang dilakukan ada penurunan tingkat insomnia pada lansia insomnia setelah diberikan terapi rendam air hangat pada kaki dari insomnia berat menjadi insomnia ringan-sedang, insomnia ringan-sedang menjadi tidak insomnia, dan insomnia berat menjadi tidak insomnia. Dibuktikan dengan hasil responden pertama mengalami penurunan insomnia dari 18 menjadi 15, responden kedua mengalami penurunan insomnia dari 18 menjadi 14, responden ketiga mengalami penurunan insomnia dari 18 menjadi 11, dan responden keempat mengalami penurunan insomnia dari 15 menjadi 11. Kesimpulan dari penelitian intervensi terapi rendam air hangat pada kaki pada lansia telah menunjukkan penurunan tingkat insomnia yang signifikan. Kata Kunci: Insomnia; Lansia; Rendam Air Hangat